Speech therapy intervention before dental management in patients with special needs: A case report - Ferraz, M. J. Pereira Coelho [UNESP]; Gomes, M. F. [UNESP]; De Batista, S. R F [UNESP]; Amorim, C. F.; Amorim, J. B. [UNESP]; Matsui, M. Y. [UNESP] (My University, 2012)
Fragile X syndrome is a cytogenetic abnormality related to chromosomal X. This syndrome is frequently associated to intellectual disability, psychological problems, as well as heart, skeletal and join alterations. Intraoral anomalies include malloclusion, ogival palate, cleft palate, presence of mesiodens, dental hypomineralization and abrasion of the occlusal surfaces and incisai edges. The study of characteristics of this syndrome is important for the dentist in order to guide dental treatment and prevention. The aim of this study is to present a myofunctional therapy protocol, evaluated by surface electromyography. A case of a 21 year-old young man who attended the Training Program in Dentistry for Persons with Disabilities, School of Dentistry of São José dos Campos/UNESP is reported. He underwent myofunctional therapy before dental treatment and the masticatory muscles were evaluated by surface electromyography. The exercises of myofunctional therapy consisted of active and passive simple movements of opening and closing the mouth, tongue protrusion and retrusion, digital manipulation and also by using an electric massager on intraoral and perioral region of the masseter, buccinator and orbicularis oris. Action potentials of the masticatory muscles decreased in almost all the muscles and values for the bite force and mandibular opening capacity increased. This study showed that brief and immediate myofunctional therapy optimized clinical practice with positive repercussion on dental care.
Keywords: Electromyography; Fragile X syndrome; Palpation; Stomatognathic system; adult; case report; cleft palate; clinical practice; clinical protocol; dental procedure; dentition; electromyography; fragile X syndrome; gingivitis; human; hypoplasia; male; muscle training; process optimization; speech therapy